H2AX phosphorylation level in peripheral blood mononuclear cells as an event‐free survival predictor for bladder cancer. Issue 11 (19th November 2015) - Turinetto, Valentina; Pardini, Barbara; Allione, Alessandra; Fiorito, Giovanni; Viberti, Clara; Guarrera, Simonetta; Russo, Alessia; Anglesio, Silvia; Ruo Redda, Maria Grazia; Casetta, Giovanni; Cucchiarale, Giuseppina; Destefanis, Paolo; et al.
Abstract : Bladder cancer (BC) has a typical aetiology characterized by a multistep carcinogenesis due to environmental exposures, genetic susceptibility, and their interaction. Several lines of evidence suggest that DNA repair plays a role in the development and progression of BC. In particular, the study of individual susceptibility to DNA double strand breaks (DSBs) may provide valuable information on BC risk, and help to identify those patients at high‐risk of either recurrence or progression of the disease, possibly personalizing both surveillance and treatment. Among the different DSB markers, the most well characterized is phosphorylation of the histone H2AX (γ‐H2AX). We assessed any potential role of γ‐H2AX as a molecular biomarker in a case‐control study (146 cases and 146 controls) to identify individuals with increased BC risk and at high‐risk of disease recurrence or progression. We investigated γ‐H2AX levels in peripheral blood mononuclear cells before and after their exposure to ionizing radiation (IR). We did not find any significant difference among cases and controls. However, we observed a significant association between γ‐H2AX basal levels and risk of disease recurrence or progression. In particular, both BC patients as a whole and the subgroup of non‐muscle invasive BC (NMIBC) with high basal H2AX phosphorylation levels had a decreased risk of recurrence or progression (for all BC HR 0.70, 95%CI 0.52–0.94, P = 0.02; for NMIBC HR 0.68, 95%CI 0.50–0.92, P = 0.01), suggesting a protective effect of basal DSB signaling. Our data suggest that γ‐H2AX can be considered as a potential molecular biomarker to identify patients with a higher risk of BC recurrence. © 2015 Wiley Periodicals, Inc.